Implementasi Kurikulum Barbasis Cinta Pada Madrasah Ibtidaiyah Nahdatul Ulama (MINU) Maslakul Falah Glagahwaru Undaan Kabupaten Kudus - Achmad Syakur (EL-EMIR Institute, 2026)
This study examines the implementation of the Love-Based Curriculum (LBC) in Islamic elementary schools within the Nahdlatul Ulama tradition, particularly at MINU Maslakul Falah, as an Islamic educational approach that emphasizes compassion, empathy, and holistic character development. A qualitative approach with a library research design was employed by analyzing scholarly articles, policy documents from the Ministry of Religious Affairs, and relevant studies published between 2020 and 2026. Data were processed through data reduction, data display, and inductive-comparative conclusion drawing to construct a conceptual model of LBC implementation. The findings indicate that the Love-Based Curriculum is grounded in five core pillars: love for God, knowledge, humanity, the environment, and the nation. Its implementation in madrasah settings is not limited to cognitive achievement but extends to affective and spiritual development through school culture, humanistic learning processes, and holistic assessment systems. The study also reveals that LBC implementation contributes to a more inclusive and disciplined learning environment while strengthening students’ character aligned with Pancasila values and the Islamic principle of rahmatan lil ‘alamin. Nevertheless, several challenges remain, including teachers’ limited conceptual understanding, lack of technical training, and uneven institutional readiness.